MENGEMBANGKAN GENERASI MUDA DIGITAL YANG BERKARAKTER POSITIF DALAM MENGGUNAKAN MEDIA SOSIAL DAN INTERNET - Fajri, Chotamul; Suci Oktaviyanti; Bella Fitriana; Ariella Aurellia Putri (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The development of information and communication technology has made social media and the internet an integral part of the lives of the younger generation. The high intensity of digital media use among students has both positive impacts and potential problems if it is not accompanied by an understanding of ethics and good character. This Community Service (PKM) activity aims to increase digital literacy and shape the positive character of the younger generation in using social media and the internet wisely and responsibly. The activity was conducted face-to-face at Muhammadiyah 25 Pamulang High School, South Tangerang City, using methods of socialization, counseling, and interactive discussion. The material presented included digital literacy, social media ethics, the impact of digital media use, and the importance of positive character building. The results of the activity showed an increase in students' understanding and awareness of the importance of ethics, responsibility, and critical thinking in digital media. Thus, this PKM activity made a positive contribution in supporting the formation of a positive and ethical digital generation in utilizing social media and the internet.